2015
DOI: 10.7860/jcdr/2015/9089.5589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Predictable Biomarkers in Conjunction to Framingham Risk Score to Predict the Risk for Cardiovascular disease (CVD) in Non Cardiac Subjects

Abstract: We conclude the application E-Selectin, leptin, OPG and Ox-LDL as biomarkers along with the framingham risk scores in prediction risk for CVD in the individuals with subclinical atherosclerosis. It is more reliable and predictable as compared to the individual biomarkers alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…This study showed that Framingham risk score used in prediction of risk for CVD in individuals with subclinical atherosclerosis was significantly correlated with OPG. In agreement with our study, Reddy et al (44) observed that the atherosclerotic biomarkers such as OPG and e-selectin, leptin and Ox-LDL were elevated among the study groups with a definite risk of CVD as compared to the control group. Pearson's correlation showed a significant association between the individual risk score (30 years FRS for CVD) of individuals, and the above biomarkers.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that Framingham risk score used in prediction of risk for CVD in individuals with subclinical atherosclerosis was significantly correlated with OPG. In agreement with our study, Reddy et al (44) observed that the atherosclerotic biomarkers such as OPG and e-selectin, leptin and Ox-LDL were elevated among the study groups with a definite risk of CVD as compared to the control group. Pearson's correlation showed a significant association between the individual risk score (30 years FRS for CVD) of individuals, and the above biomarkers.…”
Section: Discussionsupporting
confidence: 93%
“…Using an otherwise healthy cohort, we also observed that the TAC/HPX ratio was associated with the Framingham risk score (FRS), an established CVD risk predictor, which was independent of the conventional CVD risk markers such as LDL-C, HDL-C and blood pressure [ 255 ]. This association is consistent with earlier reports in which FRS was associated with other serum oxidative stress-linked biomarkers such as peroxiredoxin [ 261 ], γ-glutamyltransferase (GGT) [ 262 ], bilirubin [ 263 ], glutathione redox state [ 56 ], oxidised disulphide cysteine [ 264 ], oxidised phospholipids [ 265 ], oxidised LDL [ 266 ], 9-hydroxy eicosatetraenoic acids, and F2-isoprostanes [ 57 ]. Collectively, these data suggested that changes in plasma redox balance, especially in the preclinical stage when the person is assumed to be healthy, may reflect an individual’s early biochemical shift toward disease.…”
Section: Evidence That Changes In Lifestyle-linked Oxidative Stressupporting
confidence: 91%
“…Several risk factors have been proposed as potential markers for improved detection of subclinical atherosclerosis. In particular, physical measurements such as neck circumference [ 21 ] and abdominal adiposity [ 22 ]; inflammatory biomarkers such as C-reactive protein (CRP) [ 23 ]; lipid parameters such as oxidized LDL; adhesion molecules such as E-selectin; cytokines such as osteoprotegerin; and adipokines such as leptin [ 24 ], have all been associated with subclinical atherosclerosis in different ethnic groups. However, each of these factors provides only a rather limited information for cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%